2017
DOI: 10.1007/s40097-017-0235-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of chitosan–copper nanocomposites and their fungicidal activity against two sclerotia-forming plant pathogenic fungi

Abstract: In this report, the metal-vapor synthesis (MVS) was used for the preparation of copper nanoparticles which was then used for the preparation of chitosan-copper nanocomposite. The antifungal activity of Cu@Chit NCs against two sclerotium-forming plant pathogenic fungi Sclerotium rolfsii (S. rolfsii) and Rhizoctonia solani (R. solani) AG-4 was evaluated in vitro and their effects on hyphal morphology, and sclerotia formation were observed for the first time. The NCs were prepared through impregnation of chitosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…XRF analysis shows that the metal proportion of the Cu-carrying powders based on ChitLMW and ChitHMW is 0.5 and 0.83%, respectively. Previously, the same method for preparing Cu-carrying chitosan powders with a high copper concentration of 3–5% w / w was used [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…XRF analysis shows that the metal proportion of the Cu-carrying powders based on ChitLMW and ChitHMW is 0.5 and 0.83%, respectively. Previously, the same method for preparing Cu-carrying chitosan powders with a high copper concentration of 3–5% w / w was used [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was previously demonstrated that the surface of the composite prepared with Cu-acetone organosol contains two oxidized copper states Cu 2+ and Cu + , with concentrations (at. %) of 10.7 and 3.6%, respectively [ 20 ]. Experimental SAXS curves of Cu-carrying chitosan and pristine non-modified chitosan (ChitLMW) are described in Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical MVS reactor [1][2][3][4] has an evacuated volume of 5 l. Nickel or cobalt samples (0.3-0.5 g) are evaporated into vacuum of 10 -2 Ра with a W evaporator.…”
Section: Methodsmentioning
confidence: 99%
“…A significant advantage of the method is absence of restrictions regarding the choice of metal. By means of MVS, various types of natural polymers, such as chitosan , hyaluronic acid , and cellulose , were incorporated with metal nanoparticles. It has been demonstrated that MVS can be employed for successful preparation of gauze bandage loaded with AgNPs with pronounced antibacterial activity against S. aureus , Staphylococcus haemolyticus , P. aeruginosa , Klebsiella pneumoniae , Escherichia coli , and Moraxella spp .…”
Section: Introductionmentioning
confidence: 99%